Genotype-Phenotype Analysis and Mutation Spectrum in a Cohort of Chinese Patients With Congenital Nystagmus - Wang, Xiao-Fang; Chen, Hui; Huang, Peng-Juan; Feng, Zhuo-Kun; Hua, Zi-Qi; Feng, Xiang; Han, Fang; Xu, Xiao-Tao; Shen, Ren-Juan; Li, Yang; Jin, Zi-Bing; Yu, Huan-Yun (Frontiers in Cell and Developmental Biology, 2021)
Purpose Congenital nystagmus (CN) is a genetically and clinically heterogeneous ocular disorder that manifests as involuntary, periodic oscillations of the eyes. To date, only FRMD7 and GPR143 have been reported to be responsible for causing CN. Here, we aimed to identify the disease-causing mutations and describe the clinical features in the affected members in our study. Methods All the subjects underwent a detailed ophthalmic examination. Direct sequencing of all coding exons and splice site regions in FRMD7 and GPR143 and a mutation assessment were performed in each patient. Results We found 14 mutations in 14/37 (37.8%) probands, including 9 mutations in the FRMD7 gene and 5 mutations in the GPR143 gene, seven of which are novel, including c.284G>A(R95K), c.964C>T(P322S), c.284+10T>G, c.901T>C (Y301H), and c.2014_2023delTCACCCATGG(S672Pfs*12) in FRMD7, and c.250+1G>C, and c.485G>A (W162*) in GPR143. The mutation detection rate was 87.5% (7/8) of familial vs 24.1% (7/29) of sporadic cases. Ten mutations in 25 (40%) non-syndromic subjects and 4 mutations in 12(33%) syndromic subjects were detected. A total of 77.8% (7/9) of mutations in FRMD7 were concentrated within the FERM and FA domains, while all mutations in GPR143 were located in exons 1, 2, 4 and 6. We observed that visual acuity tended to be worse in the GPR143 group than in the FRMD7 group, and no obvious difference in other clinical manifestations was found through comparisons in different groups of patients. Conclusions This study identified 14 mutations (7 novel and 7 known) in 8 familial and 29 sporadic patients with congenital nystagmus, expanding the mutational spectrum and validating FRMD7 and GPR143 as mutation hotspots. These findings also revealed a significant difference in the screening rate between different groups of participants, providing new insights for the strategy of genetic screening and early clinical diagnosis of CN.